Optical and near-IR spectroscopy of candidate red galaxies in two z ~ 2.5 proto-clusters - Doherty, M.; Tanaka, M.; De Breuck, C.; Ly, C.; Kodama, T.; Kurk, J.; Seymour, Nick; Vernet, J.; Stern, D.; Venemans, B.; Kajisawa, M.; Tanaka, I. (EDP Sciences, 2010)
We present a spectroscopic campaign to follow-up red colour-selected candidate massive galaxies in two high redshift proto-clusters surrounding radio galaxies. We observed a total of 57 galaxies in the field of MRC0943-242 (z = 2.93) and 33 in the field of MRC 1138-262 (z = 2.16) with a mix of optical and near-infrared multi-object spectroscopy. We confirm two red galaxies in the field of MRC1138-262 at the redshift of the radio galaxy. Based on an analysis of their spectral energy distributions, and their derived star formation rates from the Ha and observed frame 24 µm flux, one object belongs to the class of dust-obscured star-forming red galaxies, while the other is evolved with little ongoing star formation. This result represents the first red and mainly passively evolving galaxy to be confirmed as companion galaxies in a z > 2 proto-cluster. Both red galaxies in MRC 1138-262 are massive, of the order of 4-6 × 1011 M?. They lie along a colour-magnitude relation which implies that they formed the bulk of their stellar population around z = 4. In the MRC0943-242 field we find no red galaxies at the redshift of the radio galaxy but we do confirm the effectiveness of our JHKs selection of galaxies at 2.3 < z < 3.1, finding that 10 out of 18 (56%) of JHKs-selected galaxies whose redshifts could be measured fall within this redshift range. We also serendipitously identify an interesting foreground structure of 6 galaxies at z = 2.6 in the field of MRC0943-242. This may be a proto-cluster itself, but complicates any interpretation of the red sequence build-up in MRC 0943-242 until more redshifts can be measured. © 2010 ESO.